Political Capital of Legislative Member Ahmad Yamin in the Legislative Elections for the 2019-2024 Period in Banyuasin - SUMAYYAH, SITI (Ampera: A Research Journal on Politics and Islamic Civilization, 2023)
This research is entitled "Political Capital of Legislative Member Election (Case Study of Ahmad Yamin's Election as Legislative Member in Banyuasin Regency for the 2019-2024 Period)." The study aims to determine the driving factors and obstacles to Ahmad Yamin's election in the legislative general election contest. Employing a descriptive qualitative research method, this study focuses on primary data, where Ahmad Yamin serves as the main actor and topic of the research, successful team members, and party cadres, while secondary data includes books, journals, documentation, and information obtained from relevant institutions related to the research problem. Data collection techniques involve observation, documentation, and interviews. The research findings indicate that Ahmad Yamin's ability to manage relationships is quite good, resulting in substantial support from the party and local residents. However, the lack of public attention to the general election poses a significant obstacle for Ahmad Yamin and his team.